Magnetic Fe3O4 Nano-Structured Coatings for Corrosion Protection of Mild Steel - Abed, Khalil Mohammed (2014)
A Master of Science thesis in Mechanical Engineering by Khalil Mohammed Abed entitled, "Magnetic Fe3O4 Nano-Structured Coatings for Corrosion Protection of Mild Steel," submitted in July 2014. Thesis advisor is Dr. Taleb Ibrahim and thesis co-advisor is Dr. Shivakumar Ranganathan. Soft and hard copy available.